Seismohydrogeological Phenomena as a Earthquakes’ Trigger Impact on Groundwater (by the Example of the Wells of the Petropavlovsk-Kamchatsky Test Site, Kamchatka Peninsula) - Kopylova G.N.; Boldina S.V. (My University, 2023)
Based on the long-term observations of the wells on the Petropavlovsk-Kamchatsky Test Site, the Kamchatka Peninsula, the paper analyzes manifestations of three main types of seismohydrogeological effects – hydrogeological precursors, coseismic pressure jumps and postseismic effects of the vibrational impact of seismic waves in measurements of the pressure and chemical composition of groundwater, depending on the earthquake parameters (magnitude, epicentre distance, intensity of seismic impact in the observation areas). The paper presents data on the earthquakes that were preceded by hydrogeological precursors in several (n = 2–4) wells. It is discussed whether it is possible to use hydrogeological precursors to predict strong earthquakes in Kamchatka. The authors also discuss the results of their experimental use in a real-time environment with weekly reports on the current observational data for the Kamchatka Branch of the Russian Expert Council. By the example of water level observations in YUZ-5 Well, the authors analyzed coseismic jumps in the groundwater pressure due to rupture formation in the sources of local Mw > 6.0 earthquakes and four types of effects of the vibrational impact of seismic waves during local and distant Mw = 6.8–9.3 earthquakes at epicentral distances from 80 to 14600 km; the study demonstrates that such effects depend on the earthquake parameters and the intensity of seismic impact in the well area.
Keywords: 37.31.19 Сейсмология; 38.61.15 Динамика и режим подземных вод; 38.61.17 Гидрогеохимия